2020
DOI: 10.3390/nano10010127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Oxide Nanoparticles on Toll-Like Receptor mRNAs in Human Monocytes

Abstract: For the widespread application of nanotechnology in biomedicine, it is necessary to obtain information about their safety. A critical problem is presented by the host immune responses to nanomaterials. It is assumed that the innate immune system plays a crucial role in the interaction of nanomaterials with the host organism. However, there are only fragmented data on the activation of innate immune system factors, such as toll-like receptors (TLRs), by some nanoparticles (NPs). In this study, we investigated T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The manuscript reports the molecular mechanisms leading to differentiated macrophage phenotypes in the presence of several metallic NPs and the following inflammatory responses. On the same topic, a research paper by Vasilichin et al shows data on the effects that these types of particles have on the expression of pattern recognition receptors (PRRs) in human monocytic THP-1, specifically the Toll-Like-Receptors (TLRs) 4 and 6 [ 2 ].…”
Section: Editorialmentioning
confidence: 99%
“…The manuscript reports the molecular mechanisms leading to differentiated macrophage phenotypes in the presence of several metallic NPs and the following inflammatory responses. On the same topic, a research paper by Vasilichin et al shows data on the effects that these types of particles have on the expression of pattern recognition receptors (PRRs) in human monocytic THP-1, specifically the Toll-Like-Receptors (TLRs) 4 and 6 [ 2 ].…”
Section: Editorialmentioning
confidence: 99%
“…Vasilichin et al investigated the influence of metal oxide NPs on innate immunity by testing TLR-4/6 mRNAs in the human monocyte cell line [ 149 ]. They found that all studied NPs activated TLR-6 expression, while AlOOH enhanced both TLR-4 and -6 expression.…”
Section: Nanoparticles and Nanoparticles-based Drug Delivery Systementioning
confidence: 99%
“…The study of functionalized magnetic nanoparticles (MNPs) has shown tremendous technological advantageous features for biomedical applications [ 6 , 7 , 8 ], such as MRI contrast [ 9 , 10 ] and drug delivery systems [ 11 ], to increase efficiency by releasing a specific drug in a target tissue, without possible damage to healthy tissues [ 5 , 12 , 13 ]. In the presence of a magnetic field, MNPs can be driven to a specific location, increasing the drug concentration [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%